Renewable Energy: Pros and Cons - Abdullah Wasmi, Abdullah Majeed; Muhammad Ali, Mohammed Athal; Yassin Rajab, Omar Saddam; Dakhil Mahjoub, Ahmed Mohammed (American Journal of Botany and Bioengineering, 2024)
The electricity generated in Iraq, which relies on fossil fuels and renewable hydropower, is insufficient to meet the country's electricity demands. Most European and industrialized countries are shifting toward renewable energy for electricity production to protect their environment from pollution caused by fossil fuels and to reduce their reliance on these finite resources. Investment opportunities are available, given the economic capabilities of the studied country. Being an oil-rich nation with substantial petroleum reserves, Iraq can allocate a portion of its oil revenues to invest in renewable energy within the country. There are obstacles to investing in renewable energy in the studied region; however, most of these challenges are minor and can be mitigated or resolved. Among the key challenges are governmental policies, which can be addressed by enacting laws that encourage both public and private sector investment in the available renewable energy resources in the region.